Instructional Leadership in Literacy-Based Learning: Enhancing Teachers’ Pedagogical Competence in Primary Schools - Tanti; Lilis Suwandari (At Turots: Jurnal Pendidikan Islam, 2026)
This study investigates the management of school principals in fostering teachers’ pedagogical competence through the implementation of literacy-based learning programs in two public elementary schools in Cianjur Regency: SDN Cikamancing and SDN Situwangi. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observations, and documentation studies involving principals, teachers, students, parents, and school staff. Data were analyzed using Miles and Huberman’s interactive model through data reduction, presentation, and conclusion drawing. The findings reveal significant differences between the two schools. SDN Situwangi demonstrated more systematic and comprehensive management characterized by strategic planning, organized literacy teams, interactive literacy practices, and reflective supervision. In contrast, SDN Cikamancing emphasized routine reading activities without structured innovation or pedagogical integration. Consequently, teacher pedagogical competence improved more markedly at SDN Situwangi, as reflected in the ability to design literacy-based lesson plans and integrate literacy across subjects. The results confirm that principal leadership is a decisive factor in enhancing pedagogical competence through literacy programs. Effective management comprising integrated planning, structured organization, diverse implementation, and developmental supervision creates a sustainable system that fosters teachers’ professional growth. This study reinforces prior findings by Ansori, Suyatno, and Sulisworo (2021); Sudiati et al. (2025) ; and Damayanti et al. (2020) , while contributing a holistic framework that links literacy initiatives to pedagogical competence development in primary education.